Venous thromboembolism during preoperative chemotherapy in the CRITICS gastric cancer trial. (31st July 2020) - Slagter, Astrid E.; Sikorska, Karolina; Grootscholten, Cecile; van Laarhoven, Hanneke W. M.; Lind, Pehr; Nordsmark, Marianne; Meershoek‐Klein Kranenbarg, Elma; van de Velde, Cornelis J. H.; van Grieken, Nicole C. T.; van Sandick, Johanna W.; Jansen, Edwin P. M.; Verheij, Marcel; et al.
Abstract: Background: The occurrence of a venous thromboembolism (VTE) is common in patients with cancer. Gastric cancer has been associated with one of the highest risks for VTE. Chemotherapy, especially cisplatin has been associated with a high VTE risk. In this study, risk factors for VTE occurrence and their potential impact on subsequent therapeutic interventions were investigated in patients who underwent preoperative chemotherapy, in the CRITICS gastric cancer trial. Patients and methods: Patients with resectable gastric cancer were preoperatively treated with three cycles of 3‐weekly epirubicin, cisplatin or oxaliplatin, and capecitabine (ECC/EOC). VTE was defined as any thrombus in the venous system, excluding superficial and/or device related VTEs. Potential risk factors were analyzed in a multivariable regression model with age, gender, Body Mass Index (BMI), tumor localization, Lauren classification, type of chemotherapy (ECC/EOC), (cardiovascular) comorbidity, and previous VTE as independent risk factors. The impact of VTE on completion rate of preoperative chemotherapy, surgical resection rate, postoperative complications, and start of postoperative therapy were investigated. Results: Of 781 patients, 78 (10%) of 781 patients developed a VTE during preoperative chemotherapy. On multivariable analysis, BMI ≥ 30 kg/m 2 and previous VTE were associated with VTE occurrence (reference BMI < 25 kg/m 2 ; OR 2.190; 95% CI 1.152‐4.164; P  = .017/previous VTE; OR 3.617; 95% CI 1.201‐10.890; P  = .022). Treatment with cisplatin was, compared to oxaliplatin, not significantly associated with VTE occurrence (OR 1.535; 95% CI 0.761‐3.094; P  = .231). VTE occurrence did not affect completion of preoperative chemotherapy, surgical resection rate, postoperative complications, or start of postoperative therapy. Conclusion: High BMI and previous VTE were independent risk factors for VTE occurrence during preoperative chemotherapy in patients with resectable gastric cancer. VTE occurrence in the preoperative setting did not affect receipt of further treatment. Abstract : High BMI and previous VTE were independent risk factors for VTE occurrence during preoperative chemotherapy in patients with resectable gastric cancer. Comparable proportions of patients proceeded to surgery and started postoperative therapy, suggesting that VTE occurrence during preoperative treatment did not affect receipt of further treatment.